The Role of International Administrative Law at International Organizations AIIB Yearbook of International Law 2020 - Quayle, Peter (AIIB Yearbook of International Law, 2020)
The Role of International Administrative Law at International Organizations, edited by Peter Quayle, is centred on the law of employment relations at international organizations, and divided into four parts. It examines the interplay between international administrative law and the jurisdictional immunities of international organizations. It explores the principles and practice of resolving employment related disputes at intergovernmental institutions. It considers the dynamic development of international administrative tribunals. It examines international administrative law as the basis for the effectiveness and integrity of international organizations. Together academics, jurists and practitioners portray the employment law that governs the international civil service and the resulting accountability of the United Nations, UN Specialized Agencies, and international financial institutions, like the World Bank and IMF. Readership: All international law practitioners, academics and students interested in international administrative law annd the resolution of employment-related disputes at international organizations, as well as those generally interested in the good governance, accountability, effectivenss and integrity of intergovernmental institutions.